An aspirin a day keeps cancer at bay - Mangesh A. Thorat (BJC Reports)
It has long been hypothesised that aspirin prevents cancer deaths by preventing metastasis. A recent study demonstrates this to be mediated through inhibition of Thromboxane A2 (TXA2) leading to reversal of suppression of T cell immunity. I appraise the context and future research implications of these findings.